Alzheimer's Disease : initial clinical implementation of automated volumetry (2014)
ABSTRACT: Alzheimer’s disease (AD) is a chronic, progressive, and degenerative brain disease. Mild cognitive impairment (MCI) may represent a transitional predementia state between normal aging and AD dementia. Noninvasive diagnostic methods are necessary to identify asymptomatic individuals and MCI subjects with high-risk genetic factors who are candidates for early preventive or therapeutic intervention.